PSYCHOLOGICAL WELL-BEING OF THE DYAD OF PARTNERS WITH DISABILITIES - Shipova, Natalya; Sevastyanova, Ulyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The relevance of the scientific problem and the scientific novelty are due to the social demand of society for studying problems related to the subjective well-being of people with disabilities. The focus of our attention is the psychological well-being of dyads in close relationships (romantic or marital). The aim of the study is to analyze the psychological well-being in a dyad of partners who are in close relationships. The article analyzes the characteristics inherent in close relations of couples in which one of the partners has a disability. Using the Scale of Adaptation and Cohesion (FACES-3)), the levels of adaptation and cohesion of the dyads were revealed. Methods Quality of life Enjoyment and Satisfaction Questionnaire examines quality of life and subjective well-being, assesses the degree of subjective satisfaction with emotional and social spheres, health, activity in free time. Particularly analyzed data of a semi-structured interview. Empirically revealed differences in the understanding of their own close relationships depending on the health status of the partner. Dyads, including partners with disabilities, demonstrate a high level of satisfaction, average cohesion values, partial balance. The study is complex, and now there is a clear prospect for its continuation.